The “medico competente” and the management of COVID-19 emergency in the first phase of the pandemic: The experience in a large chemical industry in Italy - Giuseppe TAINO; Concetta BUONOCORE; Tiziana GAZZOLDI; Francesca SOLAZZO; Irene TAINO; Alberto DELOGU (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: During the COVID-19 pandemic, Occupational Medicine (OM) has assumed a role of great responsibility in Italy. The need to prevent and manage the SARS-CoV-2 infection risk in the workplaces, has subverted the principles of OM, which is focused on the prevention and protection of occupational risks. In this perspective, the occupational physician (called “Medico Competente”) appointed by private and public companies has become a global health and safety advisor to the employer. The study aims to describe the containment strategy against COVID-19 infection adopted by a chemical industry in the Lombardy Region between February-April 2020, namely during the most critical phase of the pandemic in Italy. Methods: The population examined in our study is the entire population of a large petrochemical industrial site, totaling 670 workers. The time interval considered was the period from the end of February to the end of April 2020. A strategy was implemented for the containment of the epidemic at the production site with the collaboration of various professionals and the employees themselves. Through telephone triage, employees absent due to flu-like symptoms were assigned an initial assessment, followed by subsequent periodic reassessment to monitor the progress of their clinical status. Results: It was found that 182 workers out of a total of 670 employees were absent due to illness. Of the absent workers, 98 (54%) complained of the flu-like syndrome and 84 (46%) were absent due to other illnesses. Of the workers, 14.6% had suspected symptoms of COVID-19 during the reporting period. Discussion and Conclusion: The COVID-19 pandemic highlighted the key role played by the “Medico Competente” in protecting the health of workers and communities. During the health emergency period, OM helped keep national production active and contributed to the definition of measures to protect the health and safety of workers. In this emergency period, the “Medico Competente” was assigned new tasks and functions, which should be considered not as an aggravation of responsibilities, but as an enhancement of the professionalism and skills of the specialist in OM.